Functional variability in the takeoff phase of one metre springboard forward dives - Sayyah, M.; King, M. A.; Hiley, M. J.; Yeadon, M. R. (Human Movement Science, 2020)
In springboard diving consistency of body orientation at water entry is necessary for a good dive and is likely to be dependent on the consistency of conditions at takeoff. The aim of the present study was to investigate whether a diver modifies his technique from dive to dive during the board contact phase in order to be more consistent at takeoff in one metre springboard forward dives. Two-dimensional video analysis was used to calculate orientation and configuration angles of 12 forward pike dives and 12 forward 2½ somersault pike dives, performed by an international diver. A computer simulation model of a diver and springboard during board contact was used to obtain matching simulations of the performances and to calculate the rotation potential (angular momentum × flight time) for each dive. Simulations were used to determine the variation in conditions at maximum board depression arising from variation in touchdown conditions, and the variation in takeoff conditions arising from the variability in conditions at maximum board depression. A comparison of the simulated and performance variations implied that adjustments were made during the board contact phase for both the pike dives and the 2½ somersault pike dives. In the board depression phase, adjustments reduced the variability in the mass centre horizontal velocity at the lowest point. In the board recoil phase, adjustments reduced the variability in the horizontal velocity and rotation potential at takeoff.